Small cell neuroendocrine carcinoma presenting as inguinal hernia: A case report. (May 2021) - Quinn, Erina; Miller, Natalie; Capanegro, James; Smith, Travis
Abstract: Introduction: One of the most common surgical procedures performed annually is inguinal hernia repair. Inguinal hernias are traditionally known to be caused by a weakening in the abdominal wall and precipitated by increased intraabdominal pressure. Recently, intra-abdominal cancer producing the increased intraabdominal pressure, along with metastasis directly into the inguinal canal, have been identified in more studies as causes of inguinal hernias. Presentation of case: This case focuses on a unique presentation of small-cell neuroendocrine carcinoma presenting as an inguinal hernia. Discussion: This patient's rapid demise and advanced metastatic disease upon presentation is alarming, but his advanced disease process presenting as a routine inguinal hernia is noteworthy. Upon literature analysis, the number of advanced disease processes – most notably cancer – presenting as hernias is significant. Conclusion: This case emphasis the importance of perioperative screening, and presents the question, should hernias indicate further workup in the appropriate, at-risk patient populations. Highlights: Small cell neuroendocrine carcinoma is a highly malignant, poorly defined cancer with a wide variety of metastasis sites. The clinical presentation of intra-abdominal cancer within inguinal hernia has mounting supporting evidence. Late metastatic small cell lung carcinoma developed in inguinal hernia from an increase in intra-abdominal pressure. Further screening for malignancies in those who present for an evaluation of a hernia may be merited.